The ethics of subliminal communication - Gratz, J. E. (Journal of business ethics, 1984)
Assume that we communicate for the purpose of trying to change a person's behavior either overtly or covertly. As long as this is done in an honest manner, no concern with ethics is involved. But suppose a communication pattern — subliminals — is developed that covertly tries to change our behavior without our consent. Then, concern with ethics is involved., Very little evidence exists to support a definitive quantitative impact of subliminal communication. There is a suggestion, however, that subliminals do in fact manipulate people to do certain things. If this is so, then we have an over-riding issue in ethics — the ultimate invasion of a person's privacy — his mind.